Electrochemical study of polyaniline powder and its characterization - Nur Nabilah, Zulkifli (2012)
Polyaniline powder has been successfully synthesized which has received great attention due to its stable environment and possessing excellent electrical, optical and an electrochemical properties. Synthesizing pol'yaniline powder was conducted to estimate the electrochemical and it's characteristic. Here polyaniline powder was synthesized by oxidative polymerization with Ammonium Persulphate used as oxidant. The blue color polyaniline powder was further characterized using Fourier Transform Infrared Spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA), X-Ray Diffraction (XRD), and Cyclic Volatmmetry (CV). The FTIR spectrum shows the presence of benzoid and quinoid ring observed at 1500 cm -1 and 1600 cm-1. A shark peak centered around 25.3° and 14.7°. Thermogram of polyaniline powder shows three step of weight loss ranging from 0°C to 600°C, 15 % for the first step and 13 % for the second step. The capacitance of polyaniline powder 8 F/g was obtained. The Nquist plots shows a semicircle indicating low resistivity.